An Exploratory Study of Cantonese Learning Strategies Amongst Non-Chinese English-Speaking Ethnic Minority University Students in Hong Kong - Pun, Jack; Yu, Qianwen Joyce; Sicuan, Tom Keannu; Macaraeg, Michael Angelo G.; Cia, Joe Marc Pineda (Frontiers in Psychology, 2022)
This study investigates the strategies for learning Cantonese that are adopted by non-Chinese English-speaking ethnic minority (EM) university students in Hong Kong. The aim is to identify the challenges these students face in applying their strategies to learn Cantonese and to explore their learning experiences when implementing them. Drawing on questionnaire surveys and semi-structured interviews with 30 EM students at a university in Hong Kong, this study identifies these learners’ strategies, elicits their views on the use of these strategies and examines their learning experiences. The findings suggest that EM students are ‘medium strategy users’, with social strategies being their most commonly used types of learning strategies, followed by compensation and metacognitive strategies. The more proficient Cantonese users tend to use metacognitive strategies that promote planning and are goal-oriented. Taken together, this study sheds light on the complex interplay of sociocultural variables in shaping EM university students’ Cantonese learning experience in Hong Kong. It also highlights the importance of analyzing EM students’ linguistic repertoire and the local language ecology in understanding Cantonese learning in a multilingual context like Hong Kong.